Intentional Replantation as Treatment of Extrusive Luxation: A Case Report - Takamiya, Aline Satie [UNESP]; Figueiredo, Leonardo Raniel [UNESP]; Debortoli, Caio Vinicius Lourenço [UNESP]; Sonoda, Paulo Koji Hara; Costa, Luy de Abreu [UNESP]; Figueiredo, Cássio Messias Beija Flor [UNESP]; Sonoda, Celso Koogi [UNESP] (My University, 2022)
Accurate diagnosis, immediate care and proper treatment planning are important factors for the successful treatment of dental traumatic injuries. In extrusive luxation, postponement in treatment may lead to the need for new strategies for the resolution of unwanted consequences. The present case report describes an unusual condition of delayed treatment regarding extrusive luxation of two anterior teeth treated by intentional replantation. An 18-year-old female patient attended the Dental School for the treatment of a traumatic injury to the anterior teeth 5 days after a fall from a bicycle. Clinically, teeth #21 and #22 were extruded in incisal edges for 5 mm from their neighboring teeth, had edematous gingiva, showed grade II mobility and were painful to percussion. Radiographically, the roots were intact and the periodontal ligament space was thickened along its entire length. As immediate repositioning could not be performed, intentional replantation was recommended. After detaching the periodontal ligament, the teeth were extracted and the alveolus was curetted and irrigated with saline solution to remove the already-formed clot. After replantation, the teeth were restrained and the patient was medicated with antibiotics as well as analgesics. After 10 days, the splint was removed, the root canals were instrumented and then, filled with calcium hydroxide. After 30 days, they were completely obturated using gutta-percha. The 5-year follow-up showed root integrity, absence of mobility and normal periodontium. The outcomes of the current case report revealed that when intentional replantation was properly conducted, it could be considered an option for the treatment of extrusive luxation where the teeth were not to be immediately repositioned.
Keywords: Dental trauma; Extrusive luxation; Tooth replantation